Population density, biomass and allometric relationship of shortneck clam Paphia malabarica (Chemnitz, 1782) from estuarine regions of Goa, west coast of India - Nagvenkar, Smita Suresh; Ansari, Zakir Ali; Jagtap, Tanaji Gajanan (Indian Journal of Fisheries, 2014)
Studies on morphometry and length-weight relationship of Paphia malabarica were carried out in samples collected during March 2009 to March 2010 at two locations in Goa. Morphometric relationships between length-breadth and length-depth variables were found to be linearly related. However, the relationship between length-total weight, length-shell weight, length-wet weight and length-dry weight showed a nonlinear isometric pattern at both stations. Data also indicated significant spatio-temporal variation in the density, biomass and dimensions among clams at the two sampling stations. The clam population density was compared with relevant physico-chemical parameters and is discussed in the present study. Chlorophyll a of water sample was observed to be the major water quality parameter influencing the density of P. malabarica at both the stations.